ANALISIS KECAKAPAN BERBICARA BAHASA INGGRIS MAHASISWA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI SEKOLAH TINGGI ILMU KESEHATAN KESOSI - Dwi Meisyitah Ananda (Jurnal Nurse, 2024)
Speaking helps students develop their vocabulary and grammar skills and then improve their writing skills. Students can express emotions, ideas; tell stories; request; speaking, discussing, and demonstrating various functions of language. Talking is very important outside of class. Therefore, language speakers have more opportunities to get jobs in various organizations and companies. The aim of this research is to determine the level of English-speaking proficiency and the problems they face. For this research, the samples taken were all students studying English at the KESOSI College of Health Sciences. Data was collected through a short question and answer session using 10 quick questions. The questions are adapted from IELTS speaking part 1. After data collection, the data is calculated using a formula adapted from Brown (2004) and then classified to determine the level of ability. The classification table below is adapted from Harris (1974). Based on these results, it was found that the score was quite high. It was also found that the factors affecting their speaking skills were the fear of using incorrect grammar and lack of vocabulary.